THE EFFECTIVENESS OF THE USE OF MODERN RICE HARVESTING MACHINES (COMBINE HARVESTER) ON INCREASING THE PRODUCTIVITY OF RICE FARMERS IN TENDE VILLAGE: EFEKTIVITAS PENGGUNAAN MESIN PANEN PADI MODERN (COMBINE HARVESTER) DALAM MENINGKATKAN PRODUKTIVITAS PETANI PADI DI DESA TENDE - Heri Kurniawan; Moh. Nasir Dg Marumu; Hedrat M. Nure (International Journal of Economic Entrepreneurship and Business Management, 2024)
This study aims to find out whether modern rice harvesting machines in increasing rice harvest productivity in Tende Village have been effective. This study uses a quantitative method with a descriptive approach. Data was obtained through observation, ques tionnaires, and documentation. The data analysis used is a simple linear regression analysis. The results of this study show that the use of modern harvesting machinery has a positive and significant effect on crop productivity, which is shown by the results of a simple linear regression analysis with the equation Y = 25.172 + 0.368 which means that the value of the constant a is 25.172, the use of modern harvesting machinery (bX) is 0.368 which shows a positive direction with a significant level of 0.013. The hypothesis in this study rejects H0 and accepts H1. Therefore, from this conclusion, H0 is rejected and H1 is accepted, meaning that Modern Harvesting Machinery has a Positive and Significant Effect on Crop Productivity. Based on the results of the Overall Equipment Effectiveness (OEE) method which measures the overall effectiveness of production equipment or machinery showing an OEE result of 71.2%, we can see that the rice combine harvester machine is effective at 71.2%